The Courage of Thinking in Utopias: Gadamer's "Political Plato" - Bey, Facundo (2021)
The aim of this article is to explore Gadamer´s early reflections on Plato's utopian thought and its potential topicality. In the following section, I will show how areté, understood as a hermeneutical and existential virtue, is dialectically related to ethics and politics in Gadamer's phenomenological reception of Plato's philosophy. I argue that, in Gadamer's eyes, Socratic-Platonic self-understanding enables human beings to be aware of their political responsibilities, to recognize how they are existentially and mutually related to the others, and to dialectically clarify their own existential possibilities in order to transcend their inherited world of values. In the third section, I aim to show how these are the grounds on which Gadamer's initial thoughts on the utopian dimension of Platonic political philosophy developed, mainly through his further critical account of the works on the German 'political Plato' published in Germany between 1927 and 1933, i.e., Kurt Singer's Platon, der Gründer [1927], Julius Stenzel's Platon. Der Erzieher [1928], and Kurt von Hildendrandt's Platon, Der Kampf des Geistes um die Macht [1933]. Then, in the fourth section, I will express my own views on the relevance of reconsidering how the notions of areté, phrónesis, and andreía are already related in Plato's dialogues, complementing the insights on Gadamer's interpretation of areté in section two. My purpose is to go beyond Gadamer's reading and provide us with a more solid ground to address his late reflections on political courage and its relations with his dialectical understanding of Platonic utopia as a myth. Therefore, I will explore the problem of civil disobedience, a topic that was actually not at the centre of Gadamer's concerns, as a genuine mode of utopian political action which can enact a true deviation from the sophistic pólis and its understanding of power. Finally, in the conclusion, I will characterize Gadamer's portrait of Platonic utopia as a dialectical myth which enable human beings to recognize when politics are being reduced to mere power abuse by the State and also suggest why Gadamer's approach to utopias is still actual in the present day.